The role of the language in making Sistan history’s thaumaturgies believable - Effat Neghabi; Mohsen Vesaghati Jalal (مطالعات زبانی و بلاغی)
It seems that much of the burden of the prose's beauties has been put on the shoulders of the language. Language as an important factor in creating amazing facts and historical thaumaturgies, has a paradoxical role. On the one hand, by expanding the imagination, it enhances the literacy of historical texts in a way that it separates the readers from this real world. And on the other hand with a linguistic look in creating logic and the casual relationship, it returns the audience to the context of reality so that they at the pinnacle of enjoyment and amazement take historical thaumaturgies as the truth. This article by investigating the story of the birth of the holy prophet Muhammad from the Sistan's history shows the writer's skill in this language ability and concludes that the mentioned writer has used the paradoxical function of the language in creating literacy and transferring facts for making the thaumaturgies believable.